Matching of personality traits, emotional intelligence and social skills among dance partners in competitive dancing - Šifrar, Tina (Array, 2020)
We investigated whether there was more matching in personality traits, emotional intelligence, and social skills in better performing dance couples than in their less successful counterparts and if better- and lower-performing dancers individually have more equivalent personality traits, emotional intelligence, and social skills. Twenty-four dance couples (i.e. 24 male and 24 female dancers), performing both the Latin and standard dances at a competitive level, were included in the study. Among the measured metrics were: personality traits (using the Big Five Questionnaire), social skills (using the Interpersonal Skills Questionnaire), and emotional intelligence (using the Emotional Competence Questionnaire). When comparing differences between couples, results showed that the better dance couples were more orderly, agreeable and conscientious than the lower-performing dance couples who seemed to be more open. When comparing differences between individual dancers, results showed that the better-performing dancers tended to be older, more experienced, with a higher “competitive mileage” and better-trained bodies, more diligent with a firm belief in their success, confident in attaining their goals, and more motivated. They were also more emotionally stable – a trait that stemmed from their maturity and many years of competing. Findings obtained by our study will certainly allow us to view competitive dancers from a different, as yet undiscovered and potentially deeper viewpoint of psychology. One of the practical aspects of our research lies in understanding how to keep dance couples together for a longer time, allowing dancers to perform in unison for longer periods than would be otherwise possible.